Maghemite‐Copper Nanocomposites: Applications for Ligand‐Free Cross‐Coupling (C−O, C−S, and C−N) Reactions. Issue 21 (17th September 2015) - Sharma, Rakesh K.; Gaur, Rashmi; Yadav, Manavi; Rathi, Anuj K.; Pechousek, Jiri; Petr, Martin; Zboril, Radek; Gawande, Manoj B.
Abstract: A magnetically retrievable, efficient, and benign maghemite‐Cu nanocatalyst was synthesized from inexpensive precursors and applied for C−O, C−N, and C−S bond‐formation reactions. The obtained maghemite‐Cu nanocatalyst was characterized by various techniques such as XRD, X‐ray photoelectron spectroscopy, field‐emission gun SEM with energy‐dispersive spectroscopy, atomic absorption spectroscopy, TEM, high‐angle annular dark‐field scanning transmission electron microscopy, FTIR spectroscopy, and Mössbauer spectroscopy. Excellent catalytic activity, ease of recovery, and reusability without a significant loss of yield make the present protocol highly sustainable to deal with industrial and environmental concerns. Abstract : Magnetic attraction : A magnetically retrievable, efficient, and benign maghemite‐Cu nanocatalyst is synthesized from inexpensive precursors and applied for C−O, C−N, and C−S bond‐formation reactions. Excellent catalytic activity, ease of recovery, and reusability without significant loss of yield make the present protocol highly sustainable to deal with industrial and environmental concerns.